Bt Jute Expressing Fused δ-Endotoxin Cry1Ab/Ac for Resistance to Lepidopteran Pests - Majumder, Shuvobrata; Sarkar, Chirabrata; Saha, Prosanta; Gotyal, Bheemanna S.; Satpathy, Subrata; Datta, Karabi; Datta, Swapan K. (Frontiers in Plant Science, 2018)
Jute (Corchorus sp.) is naturally occurring, biodegradable, lignocellulosic-long, silky, golden shiny fibre producing plant that has great demands globally. Paper and textile industries are interested in jute because of the easily availability, non-toxicity and high yield of cellulosic biomass produced per acre in cultivation. Jute is the major and most industrially used bast fibre-producing crop in the world and it needs protection from insect pest infestation that decreases its yield and quality. Single locus integration of the synthetically fused cry1Ab/Ac gene of Bacillus thuringiensis (Bt) in C. capsularis (JRC 321) by Agrobacterium tumefaciens-mediated shoot tip transformation provided 5 potent Bt jute lines BT1, BT2, BT4, BT7 and BT8. These lines consistently expressed the Cry1Ab/Ac endotoxin ranging from 0.16 to 0.35 ng/mg of leaf, in the following generations (analysed upto T4). The effect of Cry1Ab/Ac endotoxin was studied against 3 major Lepidopteran pests of jute- semilooper (Anomis sabulifera Guenee), hairy caterpillar (Spilarctia obliqua Walker) and indigo caterpillar (Spodoptera exigua Hubner) by detached leaf and whole plant insect bioassay on greenhouse-grown transgenic plants. Results confirm that larvae feeding on transgenic plants had lower food consumption, body size, body weight and dry weight of excreta compared to non-transgenic controls. Insect mortality range among transgenic feeders was 66% to 100% for semilooper and hairy caterpillar and 87.50% for indigo caterpillar. Apart from insect resistance, the transgenic plants were at par with control plants in terms of agronomic parameters and fibre quality. Hence, these Bt jutes in the field would survive Lepidopteran pest infestation, minimize harmful pesticide usage and yield good quality fibre.